2022
DOI: 10.3390/machines10020126
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Spherical Robot with Rolling and Jumping Modes for Deep Space Exploration

Abstract: Complex and unknown terrains in deep space exploration present great challenges to existing exploration robots. In this paper, a multi-mode motion spherical robot with flexible motion and strong environmental adaptability is presented. The spherical robot can roll and jump by swinging the pendulum and rotating the 2-DOF frame. The structure design of spherical robot is described, and the feasibility of multi-mode motion is analyzed by establishing dynamic model and testing robot prototype. In addition, the ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Additionally, a mechanism was designed to facilitate a collaborative map exploration for a single- and multi-robot system. A simulation successfully demonstrated the efficiency of the proposed technique, which produced a new deep space exploration method for rolling and jumping spherical robots [ 36 ]. The structure design was described, and its viable motion was tested through an established dynamic model.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, a mechanism was designed to facilitate a collaborative map exploration for a single- and multi-robot system. A simulation successfully demonstrated the efficiency of the proposed technique, which produced a new deep space exploration method for rolling and jumping spherical robots [ 36 ]. The structure design was described, and its viable motion was tested through an established dynamic model.…”
Section: Related Workmentioning
confidence: 99%
“…39,40 The shell of the spherical robot is generally made of hard materials, while the soft spherical shell is deformable and lighter, and the jumping height is higher than the hard spherical shell, but the rolling controllability is poor. 41 In 2022, for the complex and unknown terrain in deep space exploration, Wang et al 42 proposed a multi motion mode spherical robot (as shown in Figure 7). The robot rolls through a pendulum and a two degree of freedom rotating frame, and jumps through an internal spring mechanism.…”
Section: Jumping Ballmentioning
confidence: 99%
“…The jumping drive module primarily consists of a mechanism box and two six-bar mechanisms, which enable the robot to jump. The specific structural design can be found in our previous work [11].…”
Section: Design Of the Structurementioning
confidence: 99%
“…The rolling drive module consists of two racks and three motors, which ar to drive the robot forward, backward, and steer. The jumping drive module pri consists of a mechanism box and two six-bar mechanisms, which enable the robot to The specific structural design can be found in our previous work [11].…”
Section: Design Of the Structurementioning
confidence: 99%
See 1 more Smart Citation